The Effects of Intermittent Noise and Whole-Body Vibration on Cognitive Performance - Dwi Astuti, Rahmaniyah; Adryanna Brilliansyah, Farreleo; Aisyah Arifna Putri, Ade (Spektrum Industri, 2026)
Work environments involving noise and whole-body vibration are known to affect human cognitive performance, particularly selective attention. The aim of this study is to identify and analyse the impact of noise level and whole-body vibration exposure duration on cognitive performance using a controlled laboratory experiment and the Stroop Task. Cognitive performance was measured by total response time and accuracy under two intermittent noise levels (65 dBA and 85 dBA) and two whole-body vibration exposure durations (5 minutes and 10 minutes). Multivariate analysis indicated that intermittent noise significantly reduced response accuracy, while longer whole-body vibration exposure slowed response time. No significant interaction between noise and vibration was observed, suggesting that each factor affects cognition through different mechanisms. This study presents novel empirical evidence on the combined cognitive effects of intermittent noise and whole-body vibration exposure assessed via the Stroop Task, an approach rarely used in prior research. This study contributes to provide a better understanding of how physical environmental stressors influence selective attention in occupational settings. From a scientific perspective, controlling noise intensity and the duration of whole-body vibration exposure are essential to minimise adverse cognitive effects at work. Future research should investigate the long-term and combined effects of exposure under more complex cognitive task conditions.